Ensuring the Reliability and Efficiency of the Power Industry in the Agricultural Sector of the Republic of Belarus in Modern Conditions - I. V. Protosovitskii; E. P. Zabello; M. A. Prishchepov; V. A. Daineko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
The necessity of improving the power supply system in the agricultural sector is substantiated by the growing share of first-category loads that require targeted reliability. Improving values of the technical and economic indicators of centralized energy generation and its transmission through main and distribution grids cannot ensure high reliability of consumers of the first category, the number of which is constantly growing in agriculture. It is noted that if the power system in outage of the generating source of the high power supply is provided by inputting the emergency reserve, then at emergency switching-off phase of the section of the mains, power supply of the consumers powered by the schemes for both radial and looped distribution network may be absent for a long period of time (several hours). The ways and methods of improving the power supply system, such as integration of a single power system with distributed generation sources, ensuring their parallel operation, load management using complex tariffs for electric energy that take into account the form of load schedules, modernization of technological processes taking into account their automation and improvement of technical and economic indicators, are considered. Taking into account the increase in electricity consumption for heating and hot water supply, we consider the option of eliminating cross-subsidization, which stimulates the interest of consumers in saving electricity and reducing the fee for electricity consumption by changing the operating modes of equipment and devices. The analysis of promising energy-saving measures in agricultural power engineering demonstrated that routine measures are being supplemented by other measures induced by the fact that power electronics and microprocessor technology have significantly advanced in their development in the agricultural energy sector over the past decades, for example, for frequency control of asynchronous motors equipped by a short-circuited rotor that has high values of energy and dynamic indicators. Since there are a number of technologies in agriculture where electric energy is used without the electric drive units application and each of the technological processes has its own requirements for the reliability and quality of electric energy, the scheme of mutual redundancy from adjacent substations using distributed generation sources and technical means of automated energy accounting, control and management of electrical loads, is considered.